Reliability of the Data and Subject Pain Levels in F-wave Recordings with Submaximal Stimulation - Sangeeta Gupta; Ramji Singh (New Advances in Medicine and Medical Science Vol. 4, 2023)
This chapter aims to evaluate the reliability of the F-wave data collected following submaximal stimulation in an effort to reduce the subjects’ discomfort levels. F-wave studies are useful electrodiagnostic procedures that play important roles in the early diagnosis of diabetic neuropathy, axonal neuropathies, and focal proximal nerve dysfunctions. F-waves have numerous clinical applications. However, the recording of F-waves necessitates repeated supramaximal stimulation, which causes discomfort in the subject. 64 healthy participants between the ages of 18 and 40 years with normal neurological examinations were included in the study. F responses from the median, ulnar, tibial, and peroneal nerves were obtained using both supramaximal and submaximal stimulation. Subjects reported their level of discomfort using a visual analogue scale. The paired t test was used to compare the mean values of F-wave minimum latency, mean latency, mean duration, persistence, chronodispersion, F/M amplitude ratio, and subject discomfort level obtained by the two approaches. P value <0.05 was considered as statistically significant. There were no statistically significant differences between the groups in the mean values of the F-wave mean latency, minimum latency, chronodispersion, and stimulus duration (p>0.05). Mean persistence, mean F/M amplitude ratio and mean subject discomfort levels, however, varied statistically significantly. Submaximal stimulation can be used to obtain F-wave data. The mean and minimum latency, chronodispersion, and duration of F-waves remain rather steady, however more stimuli may be required to obtain reliable data. Submaximal reference range would be necessary for F/M amplitude ratio and F-wave persistence. Low intensity stimulation can be preferred which is associated with less subject discomfort with valid F-wave latency values.